The Relationship of Sustainability Report with Firm Values Jakarta Islamic Index - Prayogo, Youdhi; Mutia, Agustina; Hardiningsih, Pancawati; Setiawati, Ira (Universitas Negeri Malang, 2023)
The purpose of this study is to analyze the effect of sustainability reports on the environmental dimensions, social dimensions, and governance dimensions on firm value. The research sample was conducted on the 30 most liquid Islamic stocks included in the Jakarta Islamic Index sector for the 2019-2022 observation period. Research analysis technique using multiple linear regression. The test results found that disclosure of environmental performance and social disclosure had a positive effect on firm value as reflected by the Tobin'Q and PBV models. On the other hand, disclosure of corporate governance does not have a positive effect on firm value. The Tobin'Q model shows better model fit than the PBV model. This can be seen in the coefficient of determination and the F test of the model on Tobin'Q which is greater than the PBV model. These findings make it clear that the Tobin's Q model is superior because it reflects the company's assets as a whole, reflects market sentiment, reflects the company's intellectual capital, and can overcome problems in estimating the level of profit or marginal cost.